Advancing the Nigerian health system through advanced practice nursing - Damilare Jonathan Arowolo; Oluwatosin Comfort Olarinde; Yetunde Oluwafunmilayo Tola; Bose Cecilia Ogunlowo; Oluwadamilare Akingbade (Tehran University of Medical Sciences, 2023)
Background & Aim: To meet the changing global population needs and demands of patient care, healthcare systems worldwide are under restructuring and transformation. Advanced practice nursing has been adopted in many developed countries to meet pressing issues like workforce shortage and equitable distribution of competent healthcare professionals. However, Nigeria is yet to take advantage of this initiative despite being seriously affected by these issues. This article documents the need for and prospects of advanced practice nursing in Nigeria. Methods & Materials: A descriptive theoretical and empirical literature analysis was done to explain the impact of advanced practice nursing in advancing the Nigerian health system. Results: The expertise and capacity of the nursing workforce, especially its numerical strength, can be utilized to improve Nigeria's health system and achieve the global goal of making quality healthcare accessible and available to all, thereby achieving universal health coverage. Conclusion: Elevating the competencies of nurses through investments in advanced practice nursing will make primary healthcare available to Nigerians living in poverty, rural dwellers, youth, and children, thereby reducing the burden of diseases and improving health promotion and disease prevention.